Caries in Outpatients at the Department of Child Health and Dental Clinic of the Provincial Referral Hospital (RSUPP) in Medan during 1971 - 1973 - Salim, Sahat; Siregar, Helena; Tanyati, Srinita; Simanjuntak, Santi Uli (Paediatrica Indonesiana, 2019)
Of 3,000 children with dental caries examined at the Department of Child Health and Dental Clinic of the Provincial Referral Hospital in Medan during 1971 -1973, the highest caries percentage is found in the age group of 3-9 years (74.4%); it is also noted that caries is already prevalent in the group of 1 - 3 years (6.2%). Caries can be prevented by giving fluoride topically or orally and by oral hygiene. To prevent further dental decay, conservation or extraction has to be done.